Enhancing Competitive Advantage through Business Intelligence System Adoption: A Strategic Framework for Improved Decision-Making in Organisations - Garikayi Emmanuel Gondo; Lorna B Holtman (Information Management and Technology: The Proceedings of the 10\(^th\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
This paper aims to address gaps in managerial competencies by using Business intelligence systems to enhance competitive advantage. It focuses on adopting a business intelligence system as a digital strategy to improve business intelligence and address a long-time problem of information failures in organisations. The flow of quality information to make quality decisions is often ignored when measuring competitive advantage, yet, the quality of the information received by decision-makers can have a huge impact on the performance of an organisation. The question remains: How are managers getting the information to make decisions in this technological era? In some instances, information sent to decision-makers is still being prepared manually contrary to the demands of the fourth and the upcoming fifth industrial revolution where managers are expected to interact with gadgets. This paper explored ways of ensuring that managers can develop BI reports and configure the BI system to report directly to them to improve business intelligence. It answers the following questions: Do managers have the capacity to configure gadgets to report to them directly? What should be done to achieve this? We conducted qualitative research, to get a deep understanding. The results revealed that senior managers still over-rely on information supplied by humans, often prone to manipulation and errors. Supervisors try to block the free flow of information through a behaviour called gatekeeping. Senior managers lack the technical skills to develop BI reports in the BI system. This paper proposes the stages an organisation goes through to overcome this challenge. The practical implications of the findings suggest that, when BI systems are implemented effectively and utilized correctly, they contribute to informed decision-making and enhance competitive positioning in organisations.